Satisfactory Pain Management With Minimal Opioid Use After Arthroscopic Rotator Cuff Repair - Kirsten D. Garvey, M.S; Natalie A. Lowenstein, B.S; Lauren E. Piana, M.D; Kaetlyn R. Arant, B.A; Yuchiao Chang, Ph.D; Elizabeth G. Matzkin, M.D (Elsevier, 2021)
Purpose: To evaluate patient use of opioids following arthroscopic rotator cuff repair, including the number of days and number of pills when used in combination with non-opioid medications and to determine whether patients were satisfied with their pain management and if variables such as age, sex, body mass index, duration of symptoms, anticipation of postoperative pain, preoperative opioid consumption, size of the rotator cuff tear, or anxiety/depression affected pain management. Methods: This was a prospective cohort study of 117 prospectively enrolled patients older than the age of 18 years undergoing primary arthroscopic rotator cuff repair. All patients completed preoperative and 2-week postoperative questionnaires to assess their pain and satisfaction with pain management. Univariate and multivariate analyses were performed to evaluate the association of patient characteristics with satisfaction of pain control and amount/duration of opioids postoperatively. Results: Patients required a median of 18 opioid pain pills or 135 morphine milligram equivalents (interquartiles, 6-35 pills) postoperatively over 6.9 ± 5.1 days. In total, 65% of patients took opioid pain medications for 7 days or fewer. On postoperative day 2, patients reported a VAS pain score of 6.6 ± 2.8 and at the 2-week postoperative visit, mean visual analog scale pain score was 3.5 ± 2.5. Differences in age, sex, body mass index, duration of symptoms, anticipation of postoperative pain, preoperative 2-item Patient Health Questionnaire, 2-item Pain Self-Efficacy Questionnaire, current opioid use, and surgical characteristics had no effect on, or association with, satisfaction with pain management postoperatively. Conclusions: Following arthroscopic rotator cuff repair, patients can achieve satisfactory pain control using a multimodal approach with a median of 18 opioid pills (range 6-35 pills) over 6.9 ± 5.1 days when used in combination with non-opioid pain medications. Overall, 74.4% of patients were satisfied with their postoperative pain management. Level of Evidence: Level II; Prospective cohort study.